Chemicals evaluation of selected insecticides against thrips (Scirtothrip dorsalis) on chilli / Muhammad Amir Shahmi Zomri - Shahmi Zomri, Muhammad Amir (Faculty of Plantation and Agrotechnology, 2015)
The chili thrips, Scirtothrips dorsalis, is a significant pest of a various ornamental crops and tropical fruits. This pest becoming widely distributed in tropical, subtropical and temperate area. The experiment was conducted in order to evaluate the treatment water (control), confidor (a.i. Imidacloprid) , and oshin (a.i. Dinotefuran) at their recommended field doses against sucking insect pests of thrips (S. dorsalis). The result showed that confidor treatment were the most effective in controlling pest S dorsalis rather than oshin and water treatment. It is recommended for using confidor (Imidacloprid) in controlling thrips because confidor treatment have the lowest mean number among treatments for both application times.